Ecosafety Screening of Photo-Fenton Process for the Degradation of Microplastics in Water - Piazza, Veronica; Uheida, Abdusalam; Gambardella, Chiara; Garaventa, Francesca; Faimali, Marco; Dutta, Joydeep (Frontiers in Marine Science, 2022)
Microplastic pollution is receiving increased attention due to the realization of its hazards to aquatic and human life. Researchers across the globe are attempting to remove microplastics before its entry into the ecosystem. Therefore, the present work focused on the removal of microplastic from water and studied the potential risks for marine organisms and the ecosystem. The removal of model microplastics, polypropylene (PP) and polyvinyl chloride (PVC), has been studied by using photo-Fenton process. ZnO nanorods coated with SnOx(x˂2) layer and decorated with zero valent iron (Fe0) nanoparticles was used as heterogeneous catalyst for the removal of the microplastics in continuous water flow device. The obtained results demonstrated that high degradation efficiency of PP and PVC microplastics was achieved in a relatively short time and more than 95% of the average particle volume was reduced after one week of irradiation. The environmental impact of the photo-Fenton process of the microplastics degradation was investigated by using an ecotoxicological approach. An ecosafety screening has been performed through a series of experiments (bioassays) under controlled conditions, testing water samples after the photo-Fenton degradation of microparticles using a lab scale device. The ecotoxicological impact has been investigated by applying a battery of certified bioassays (UNI EN ISO/EPA standardized techniques) on aquatic organisms at different trophic levels (bacteria, algae, invertebrates). The results obtained on the three model organisms (A. fischeri, P. subcapitata and D. magna) revealed no toxic effect for samples collected both before and after the photo-Fenton process, thus showing the absence of toxic by-products development during the degradation process.